Looking Like a Russian - Ольга Юрьевна Гурова (Journal of Economic Sociology, 2013)
The paper focuses on how Russian migrants living in Finland construct their own “ethnic affiliation” through clothing styles or “style repertoires”. Representations of Russian migrants in transnational consumer culture are limited to stereotyped images, cultivated by mass media. However, these descriptions do not cover the variety of migrants’ style practices even slightly. Using intersectionality approach, the author examines the differentiation in migrants’ clothing styles. Research arguments are derived from 19 leitmotiv interviews with Russians living in metropolitan areas of Finland. Research findings demonstrate the peculiarities of “Russian” style repertoire. They include Russians’ aspiration to dress up for others, conspicuous consumption even in everyday situations, accents on details of clothes. Style repertoires may reflect certain stereotypical views on what it means, “to look like a Russian” or the reverse may be true. In this alternative case migrants demonstrate either hybrid style patterns or local variations. Differentiation of style practices depends on the length of stay in a host culture, matrimonial status, experience of living abroad, etc. In addition, the author shows that reproduction of style repertoire closely intertwined with migrants’ social characteristics. Choice of one or another way of dressing is shaped by class, profession, gender and age. Thus, in many respects, ethnic affiliation, as expressed in consumption is constructed within the context of other social dimensions.